Silicoaluminophosphates Number 5 (Sapo-5) Zeolite Templated By Imidazolium Compounds As Catalyst For Friedel-Crafts Acylation Of 2-Methylfuran - Auwal, Ismail Alhassan (2021)
Silicoaluminophosphate number 5 (SAPO-5) is one of the most extensively studied microporous solid due its application as commercial solid acid catalyst. However, its weak-to-mild acidity limits its catalytic activity in many industrially important organic reactions. The objective of this research is to synthesize SAPO-5 catalyst using new imidazolium-based structure-directing agents (SDAs) for producing furan-based biofuel via Friedel-Crafts acylation of 2-methylfuran with acetic anhydride. The study began with the synthesis of three types of imidazolium compounds bearing different functional groups, viz. 1-propyl-2,3-dimethyl-1H-imidazole-3-ium ([pmIm]+), 1-benzyl-2,3-dimethyl-1H-imidazole-3-ium ([bzmIm]+) and 3-(2,3-dihydroxypropy)-1,2-dimethylimidazolium ([dhmIm]+) to be used as SDAs to crystallize SAPO-5. The microscopic and spectroscopic analyses showed that the polarity and molecular geometry of imidazolium SDAs significantly governed the physicochemical properties of the resulting SAPO-5 products (e.g. porosity, surface area, particle size, and morphology). Among the SDAs, the [dhmIm]+, which has the highest hydrophilicity/polarity, demonstrated fastest crystallization rate of SAPO-5 due to its diol group that withdraw electron density from imidazolium ring, thereby increasing the templating effect. Next, the effects of each synthesis parameters (temperature, heating time, molar ratios of P2O5, [bzmIm]2O SDA, SiO2, and H2O) on the crystallization process is also investigated. The results indicate that the synthesis parameters influence the crystallization rate, purity, crystal size and morphology